"Won't somebody please think of the children": Are we ignoring 15 to 17 year olds in health research and health care? - James, Philip; Nash, Michael; Comiskey, Catherine (My University, 2024)
Aim and background: The authors completed a systematic literature review on barriers and enablers to under 18s accessing substance use treatment. Reviewing research against the inclusion/exclusion criteria presented challenges due to the diverse and arbitrary age categories used in research samples. This presentation illustrates these arbitrary age categories and the effect they have on research and practice. Methods: Six databases were searched (CINAHL, EMBASE, ERIC, MEDLINE, PsycINFO and Web of Science) in April 2022. Searched terms were based on population (under-18s), treatment (for SU), access (healthcare access/referral) and barriers or enablers, using subject terms where available. Articles were imported to Covidence and 3,823 abstracts were screened and 161 full texts were reviews by two reviewers. As this was secondary use of published data ethics approval was not sought. Findings: Initially 21 articles were included as they met the criteria of reporting on under 18s. Following discussion it was decided to include 6 other studies which included articles on populations aged 18 and under as it was deemed that 18-year-olds are largely similar to under 18s as they typically live with parents and are in school. Thirty-five studies were excluded as they mixed findings related to teenage children with adults aged up to 50. Ireland has considerable challenges in providing child and adolescent mental health services. Blurring of the child-adult categories limits services' ability to apply research findings in practice. Furthermore, Government and service policies reflect this confusion with proposals to treat 25 year olds in CAMHS. Conclusion: Under 18s are children and including them with adults, in research or practice, dilutes their experience and does them a disservice. Health services policy needs to consider how to manage the dichotomy between children and adults. In practice, applying evidence based findings to 15-17 year olds is particularly challenging.
2nd International Research Conference: Empowering Care: Innovations in Healthcare for a Sustainable Future
Keywords: Child centred research questions, study design, data analysis; Mental health nursing; Promotion of child centred research